Bathala: A feasibility study on germicidal dry bath lotion - Almario, Phoebe Stacey M., Avila, Alexandre Miguel P., Cortes, Jester Paul D., Escudero, Ralph Adriell M., Martin, Joyce Ann A., Mosquito, Caezar Adrian B., Pamaran, Rufino D. III., Rosales, Gabriel Leoj B., Timan, Pranz Edrian P. 4 0 16; 5
ABSTRACT: Reports of call to action by government entities such as the Manila Water Foundation (The Manila Times, 2022) which details the need for measures toward increased water conservation. This is in line with the inherent need for the fulfillment of sanitation needs that come with the Philippines undergoing the process of developed urbanization throughout its regions. In line with these statements, the researchers focus on the development and selling of a hygienic dry bath lotion wherein the firm will be based in Tondo, Manila, Philippines. It will make use of locally sourced ingredients to develop a dry bath cleanser that contributes to water conservation efforts as an alternative to the usual soap and water solution to personal hygiene. Research conducted in the paper analyzes and describes a potential market derived from competitors that is worth many millions. The researchers will develop their own product that may revolutionize self-hygiene practices in the nation. Notable is the fact that production itself of the BATHala product is outsourced from the firm of FFC Nutrition Inc., but the firm of BATHala handles all the other aspects of business, such as the marketing and selling of the product to general consumers. The researchers explore in this paper the possibility of the concept of BATHala to be a revolutionary new product in the hygienic care market that is accessible for all at a reasonable price for Filipinos. Keywords: Dry Bath Lotion, Water Conservation, Sefl-Hygiene, Locally Sourced Ingredients
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2